The discourse marker mos in rural varieties of Afrikaans in the Western Cape: A descriptive study of syntactic patterns and pragmatic function - Jantjies, Wesley (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MA (General Linguistics))--University of Stellenbosch, 2009.